Uphill running at iso-efficiency speed - Padulo, J.; Annino, G.; Smith, L.; Migliaccio, G. M.; Camino, R.; Tihanyi, J.; D'Ottavio, S. (International Journal of Sports Medicine, 2012)
The purpose of this study was to investigate the effects of slopes (0%, 2% and 7%) on temporal gait kinematics during running at iso-efficiency speed (IES). 65 male marathon runners were selected for this study. A single digital camera (210 Hz) was used to record motion; Dartfish5.5Pro was used to perform 2-dimensional (2D) video analysis and heart rate was recorded during the test. The parameters considered in this study were: step length (SL), flight time (FT), step frequency (SF), contact time (CT) and heart rate (HR). The results showed SL, FT and SF decreased as a result of the increasing treadmill gradient; SL=[(0-2%=8.38%, p<0.0001), (0-7%=23.61%, p<0.0001)]; FT=[(0-2%=8.92%, p<0.02), (0-7%=23.40%, p<0.0001)]; SF=[(0-2%=1.18%), (0-7%=4.02%, p<0.001)]. The CT and HR however increased with the increasing gradient CT=[(0-2%=9.06% p<0.0001), (0-7%=25.64%, p<0.0001)]; HR=[(0-2%=1.65%), (0-7%=3.58%)]. These results show a different trend of the footstep's kinematic parameters when running on a slope at IES. Moreover, we can calculate the optimal run speed on a slope without increasing the metabolic demand.